Validation of Scales of Stress, Fatalism and Concern About Contagion of COVID-19 in Mexican Teachers - Luna Pérez, David Gabriel (Consorcio de Universidades Mexicanas A.C., 2023)
COVID-19 has shown negative consequences on the mental health of teachers, especially because of the implementation of a gradual return to mostly face-to-face activities. The objective of the study was to identify the factorial structure of the instruments: COVID-19 Concern Scale (EPCov-19), Pandemic-Related Perceived Stress Scale of Covid-19 (EEP-10-C), and the Fatalism by COVID-19 Scale (F-COVID-19) in Mexican teachers at high school, higher and postgraduate levels. Method. 276 teachers from different states of Mexico, from 24 to 77 years old participated (M = 46.88; SD = 10.62) who answered an identification form, the EPCov-19, EEP-10-C and F-COVID-19. The construct validity of the scales was calculated through exploratory and confirmatory factor analysis, prior to these, a parallel analysis was carried out. Internal consistency was obtained using Cronbach's α and McDonald's ω. Results. It was detected that each of the scales has a unifactorial structure, which explains between 53% and 78% of the variance and has a high to very high internal consistency. Conclusions. The scales have adequate psychometric properties and can be used in Mexican teachers.